A mid-Holocene pollen record of mangrove diversity on the coast of Ujung Genteng, the southern edge of Sunda Shelf, Indonesia - SEPTRIONO HARI NUGROHO; YAN RIZAL; YAHDI ZAIM; EKO YULIANTO; PURNA SULASTYA PUTRA; AGUS MEN RIYANTO; AMAR AMAR (Society for Indonesian Biodiversity, 2024)
Abstract. Nugroho SH, Rizal Y, Zaim Y, Yulianto E, Putra PS, Riyanto AM, Amar. 2024. A mid-Holocene pollen record of mangrove diversity on the coast of Ujung Genteng, the southern edge of Sunda Shelf, Indonesia. Biodiversitas 25: 3653-3664. The Sunda Shelf provides the most informative data for studying mangrove ecosystems. However, the southern edge of the Sunda Shelf adjacent to the Sunda megathrust zone has yet to be studied. This study aimed to provide a paleoecology record of the Ujung Genteng mangrove ecosystem during the mid-Holocene (over 6,300 cal year BP (Before Present). We looked at changes in a mangrove ecosystem using pollen and radiocarbon data from the UG 7B core. Rhizophora sp. initially dominated at c. 6,200-6,100 cal year BP. The ecosystem gradually declined, transitioning to a back mangrove environment. A decrease in the mangrove and back mangrove pollen since 4,200 cal year BP, indicating a shift away from the mangrove forest. In contrast, higher non-mangrove pollen frequency indicates a closer distance to the lowland. By 400 cal year BP, all mangrove pollen vanished, and the environment became almost completely terrestrial. The implications of this research contribute to improved insights into mangrove resilience and resistance to environmental and anthropogenic stressors, aiding effective coastal management and adaptation strategies. Our study also highlights the unique conditions of Sunda Shelf paleoecology, contributing to a more comprehensive regional knowledge and offering an important reference for further investigations on coastal ecosystem dynamics.